Electrophoretic deposition of gentamicin-loaded bioactive glass/chitosan composite coatings for orthopaedic implants - Pishbin, Fatemehsadat; Mourino, Viviana; Flor, Sabrina; Kreppel, Stefan; Salih, Vehid; Ryan, Mary P.; Boccaccini, Aldo R. (ACS Applied Materials and Interfaces, 2014)
Despite their widespread application, metallic orthopaedic prosthesis failure still occurs because of lack of adequate bone-bonding and the incidence of post-surgery infections. The goal of this research was to develop multifunctional composite chitosan/Bioglass coatings loaded with gentamicin antibiotic as a suitable strategy to improve the surface properties of metallic implants. Electrophoretic deposition (EPD) was applied as a single-step technology to simultaneously deposit the biopolymer, bioactive glass particles, and the antibiotic on stainless steel substrate. The microstructure and composition of the coatings were characterized using SEM/EDX, XRD, FTIR, and TGA/DSC, respectively. The in vitro bioactivity of the coatings was demonstrated by formation of hydroxyapatite after immersion in simulated body fluid (SBF) in a short period of 2 days. High-performance liquid chromatography (HPLC) measurements indicated the release of 40% of the loaded gentamicin in phosphate buffered saline (PBS) within the first 5 days. The developed composite coating supported attachment and proliferation of MG-63 cells up to 10 days. Moreover, disc diffusion test showed improved bactericidal effect of gentamicin-loaded composite coatings against S. aureus compared to control non-gentamicin-loaded coatings. © 2014 American Chemical Society.
Keywords: bioactive glass; chitosan; coatings; drug delivery; electrophoretic deposition; gentamicin